Incidence of the ASXL1 gene in myeloid panel testing of AML and MDS patients - Karakoyun, Hilal; Yirmibes, Seren; Milas, Ceyda; Yararbas, Kanay; Sahin, Deniz Goren; Sayar, Ceyhan; Yucel, Yazgi; Arat, Mutlu (SPRINGERNATURE, 2024)
56th Annual Conference of the European-Society-of-Human-Genetics (ESHG), Glasgow, SCOTLAND, JUN 10-13, 2023